Strengthening Islamic Law of Financial Literacy Through Integrating Local Wisdom in West Nusa Tenggara Communities (ADDIN, 2025)
Most people in West Nusa Tenggara have limited understanding of the concepts and benefits of Islamic finance. This article aims to present an innovative approach to strengthening Islamic law of financial literacy through the use of local wisdom in NTB. In addition, this study aims to explore an innovative approach to strengthening Islamic financial literacy by integrating elements of local wisdom rooted in the traditions and cultural practices of NTB communities. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and document analysis involving local religious leaders, community elders, and financial practitioners in Bima, NTB. The findings reveal that incorporating local wisdom, such as customary gatherings, storytelling traditions, and culturally embedded values like gotong royong (cooperation) significantly enhances community engagement and understanding of Islamic financial principles. These culturally contextualized approaches foster a sense of relevance and trust, thereby increasing the effectiveness of financial education efforts. The study concludes that integrating local wisdom into Islamic financial literacy programs offers a culturally responsive strategy to promote financial inclusion and economic empowerment in NTB. The findings have practical implications for policymakers, educators, and financial institutions aiming to design more inclusive and locally grounded Islamic financial literacy initiatives.